O znaczeniu kształcenia kameralnego muzyków = The Importance of Teaching Chamber Music to Musicians - Marchwiński, Jerzy (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The article contains very personal perception of the so-called chamber music and the education in this area. The paper provides kind of instruction in ensemble performance and education. The opinions are based on experiences from half of century of educating young and talented musicians.
Keywords: zespół; wykonawstwo; kształcenie; muzyka kameralna; ensembles; performance; education; chamber music